Student Center Learning Design : Development of Human Rights Textbooks Based on Case Method and Team Based Project - Alfiandra, Alfiandra; El Faisal, Emil; Mariyani, Mariyani; Sonada, Rilda; Qonita, Hanifah; Agustin, Salsa (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to design learning through textbooks based on case methods and team-based projects in Human Rights courses. The research method used Design design-based research, with data collection techniques such as questionnaires and documentation. The sample in this study was 23 students from the civic education study program, at Sriwijaya University. This study analyzed data using quantitative descriptive methods. The results of the study obtained that 1) the problem analysis phase obtained the results that the results of the analysis of needs and materials showed that learning based on case methods and project-based teams was still not well facilitated; 2) the development phase, a prototype of a textbook was obtained which contained efforts for case method and project-based team learning with assignments in each Course Learning Achievement that analyzed cases and group projects to complete assignments; 3) the trial phase was carried out and input was obtained before being used on a large scale; 4) the reflection phase obtained the results that at this stage the lecturer still had to have a role and competence so that learning could be by the objectives of presenting textbooks based on case methods and project-based teams. The implications of this research have an impact on the ability of lecturers to design learning that improves critical thinking skills in solving problems and realizing the results of thinking into real learning activities.